PENGARUH INDEPENDENSI MEKANISME CORPORATE GOVERNANCE KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Siti Musyarofah, 08.05.52.0092; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2013)
Inperforming its duties, the auditor memperlukan confidence in the quality of services rendered to the user. It is important for users of financial statements to look at Public Accounting Firm (KAP) as an independent and competent party, because whether or not will affect the valuable services that have been granted by the KAP to pemakia. If users feel KAP provides a useful and valuable services, then the value of audit or audit quality also improved, so that KAP is required to act with high professionalism. This study aims to analyze the effect of independence, the mechanism of corporate governance and audit quality to the financial reporting integrity.Sample of this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in the period 2008-2010, in accordance with the criteria set and obtained as many as 41 companies. This study uses multiple linear regression analysis and hypothesis testing using t test were used to analyze the influence of independence, the mechanism of corporate governance and audit quality is partially (individual) for the integrity of financial statements. Survey results revealed the independence and audit quality significantly affect the integrity of financial statements while the corporate governance mechanisms haven significant effect.Keywords: independence, the mechanism of corporate governance, audit quality, the integrity of financial statements